Cross Sectional Study; Identifying Physical Activity Barriers Amongst Teenagers Who Are Obese/Over Weight by Appearance in Islamia College for Boys and Jinnah College for Women Peshawar - Anam Amin, Ghazi Farman, Aalia Amjad, Awais Ahmad, Shahmir Arif, Mashal Jamil, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Physical activity is defined as any bodily movement that requires the use of energy, where it is recommended, that teenagers get 60 minutes of moderate to severe physical activity. However, almost majority of the teenagers around the globe are getting inadequate physical activity. Objectives: To analyze social, cultural and religious factors that aﬀect physical activity. To identify diﬀerent personal factors such as body image, self esteem and their eﬀects on physical activity. To identify ecological and academic factors leading to decrease physical activity and its associated comorbidities. To identify the role of government in evaluating the availability of sports centres and other facilities for adolescents /teenagers. Study Design: A cross sectional study Place and Duration: Conducted Jinnah College Peshawar and Islamia College Peshawar, during from the period March 2018 to May 2018. Methodology: Sample under study was based on teenage students (16 to 19 years) with a total size of 150 students that were part of bachelor program (BS Botany) , who were obese or over-weight by appearance. The students were given standardized questionnaires randomly, regardless of gender. Collected data obtained from questionnaire were analyzed. Results: According to the results, 94.41% students had barriers to physical activities while 5.68% had none. 75 students (50%) said that they did not have any previous bad experiences with their appearance while 30 students (21.7%) said that they did. More- over, 59 students (39.3%) said that their reduced activity was due to lack of time while 55 students (36.7%) felt that the lack of safe places was the causative factor. 60 students (40%) students felt that they needed a partner while 57 students (38%) just felt de-moti- vated. Conclusion: On the basis of this study, we conclude that majority of the students have various barriers regarding their physical activities. 94.31% of the students reportedly have barriers while 5.69% had no barrier whatsoever, and they were well aware of the consequences such as obesity, diabetes etc. Keywords: Physical activity, Barriers, Over-weight, Obese.